Impact of multiple MEFV variants of unknown significance on the diagnosis and clinical presentation of familial Mediterranean fever - Dai Kishida; Masahide Yazaki; Akinori Nakamura; Ayako Tsuchiya-Suzuki; Takanori Ichikawa; Yasuhiro Shimojima; Yoshiki Sekijima (Immunological Medicine, 2024)
The detection of variants of unknown significance (VUS) in familial Mediterranean fever (FMF) is common; however, their diagnostic value remains elusive, and the interpretation of multiple VUS remains difficult. Therefore, we examined FMF diagnosis-associated factors 1-year post-genetic testing in patients with only VUS and assessed the impact of multiple VUS on diagnosis and clinical features. A 1-year follow-up was conducted on patients clinically suspected of having FMF without confirmatory diagnosis owing to the presence of only VUS. Clinical features were compared between patients with a single VUS and those with multiple VUS among patients diagnosed with FMF. Among 261 patients followed up, 202 were diagnosed with FMF based on clinical judgment. No specific clinical symptoms or variant patterns at genetic testing were associated with diagnosis at 1 year. Multiple VUS was significantly and independently associated with a lower response to colchicine than single VUS among patients diagnosed with FMF. However, clinical symptoms showed no correlation with the number of VUS. In conclusion, predicting FMF diagnosis 1-year post-genetic testing in patients with only VUS remains challenging. Moreover, the impact of multiple VUS on FMF may be limited owing to the lack of correlation with clinical features, except colchicine response.